UJI TAKARAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL VARIETAS JAGUNG (Zea mays L.) - Octavianto, Nanda Gerry; Nurhayati, Dewi Ratna; Siswadi, Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2021)
Maize is one of the most important food crops in the world and is even loved by people in Indonesia.This research was conducted in Manyaran Wonogiri, Central Java, from April to July 2020 in a pandemic situation. Where the implementation of regional PSBB is applied so that there are obstacles in the treatment of corn this research. In the cultivation of corn there are still obstacles from pest attack to harvest. The purpose of this study was to test the amount of cow manure against corn varieties (Zea mays L.). The method used in this study is RandomIzed Group Design Complete with two factorials, namely 2 varieties and 5 measure of cow manure combined into 10 combinations and repeated 3 times so that 30 experimental units were obtained. For the following treatment: J1P0: Maize P21 measure 0g/ plant, J1P1: Maize P21 measure 150 g / plant, J1P2: Maize P21 measure 300 g / plant, J1P3 : Maize P21 measure 450 g / plant, J1P4: Maize P21 measure 600 g / plant, J2P0: Corn Bisi 2 measure 0 g / plant, J2P1: Corn Bisi 2 measure 150 g / plant, J2P2: Corn Bisi 2 measure 300 g / plant, J2P3: Corn Bisi 2 measure 450 g / plant, J2P4: Corn Bisi 2 measure 600 g / plant. The results showed that the application of cow manure to Pionner 21 corn had no significant effect on observed parameters such as plant height, dry weight of stover, number of leaves, stem circumference, wet stover, but had an effect on seed weight per plantt, ear weight per plant, weight of 1000 seeds. Whereas Bisi 2 corn had no effect on plant height, leaf number, stem circumference, stover dry weight, cob weight per plantt, but had an effect on wet stover weight, seed weight per plant, weight 1000 seeds.